2015
DOI: 10.4103/0974-7796.148611
|View full text |Cite
|
Sign up to set email alerts
|

Reporting ureteroscopy complications using the modified clavien classification system

Abstract: Objective:Perioperative complications are one of the surrogate indicators of surgical outcomes. However, reporting these complications need a precise grading system. Our aim is to report and grade the complications of semirigid ureteroscopy in ureteral stone management according to the modified Clavien classification system.Materials and Methods:This is a prospective study conducted From January 2012 to June 2013. All patients with ureteral stones who were indicated for semirigid URS were evaluated. All proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 26 publications
1
28
1
6
Order By: Relevance
“…Another possible limitation is linked to the Clavien–Dindo classifications system, and we may have suffered underreporting in minor self-limiting complications as described by Ibrahim [2]. One of these underreported self-limiting complications may be mucosal damage, and there is some debate whether or not mucosal damage is simply part of the procedure, or a complication worth mentioning and grading [8, 11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible limitation is linked to the Clavien–Dindo classifications system, and we may have suffered underreporting in minor self-limiting complications as described by Ibrahim [2]. One of these underreported self-limiting complications may be mucosal damage, and there is some debate whether or not mucosal damage is simply part of the procedure, or a complication worth mentioning and grading [8, 11].…”
Section: Discussionmentioning
confidence: 99%
“…Most important complications of ureterorenoscopy are up-migration [1, 2] of stones, higher retreatment rates [1] due to incompletely removed stones (specifically in larger stones), and damage to the ureter [13] (from minor mucosal damage to avulsion) as a consequence of access sheath placement or difficulties with negotiating the ureter and rarely due to repetitive in and out movement of instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the reported complications were minor. However, some investigators [18,28] reported major complications in the form of ureteral perforation and even sepsis that required laparotomy. In our study, no ureteral perforation or avulsion was encountered, and we only had 4 (2.4%) cases of stone migration.…”
Section: Discussionmentioning
confidence: 99%
“…Sex was detected as an important entity only in grade I complications. In the previous literature, sex-associated complications were not reported according to the grade of the MCCS and there were no significant differences between sex and complication rates (3,24,25). Moreover, the association of sex with hematuria after URS was not investigated before.…”
Section: Discussionmentioning
confidence: 97%